Imprinted Poly(o-phenylenediamine-co-aniline) Electrode for Warfarin Assay in Human Samples by Differential Pulse Voltammetry - Nateghi, M.R.; Mosslemin, M.H.; Hakimi, A.; Kavoosi, S. (Asian Journal of Chemistry, 2010)
In the present paper, a modified electrode utilizing molecularly imprinted polymer (MIP) of ophenylenediamine- co-aniline (o-PDA-co-AN) was employed for the measurement of warfarin. The effective factors on the electrode response such as ratio of aniline to o-phenylenediamine concentration, warfarin content as a template, thickness of the polymer, pH of measurement solution, accumulation time and potential applied to electrode, were optimized. Measurement was performed in three stages; electrode preparation, warfarin accumulation and differential pulse voltammetry within the potential range of 0.0 to -1700 mV. Present findings showed that the peak pertaining to the reduction of C=O double bond was observed at about -1280 mV, in Britton-Robinson buffer with pH = 2.0. The calibration plot was linear over the concentration range of 10-6-10-4 M of warfarin sodium in Britton-Robinson buffer at pH = 2.0 with sensitivity of 89.8 nA μM-1 and good repeatability lower than 7.7 %. Limits of detection and quantitation for seven sequential measurements of blank solution were 6.22 × 10-8 and 2.05 × 10-7 M, respectively. The modified electrode was successfully used for warfarin measurement in pharmaceutical formulation and human serum.